Dynamics of quality of life of head and neck cancer patients after treatment. Clinical significance - A. V. Karpenko; R. R. Sibgatullin; A. A. Boyko; M. G. Kostova; O. M. Nikolayeva; E. M. Trunin (Опухоли головы и шеи)
The study objective is to evaluate the quality of life as one of the main parameters that determines the effectiveness of treatment of patients with head and neck squamous cell carcinoma.Materials and methods. Thirty-three stage III—IV oral cancer patients aged between 39 and 70 years were asked to fill EORTC QLQ-C30 (European Organisation for Research and Treatment of Cancer quality of life questionnaire core 30-questions) and QLQ-H&N35 (head and neck cancer-specific module) before and 12—18 months after completion of the treatment that consisted of surgery followed by radiation with or without chemotherapy. Surgery included neck dissection with removal of the primary tumor via transoral (n = 5) or combined (n = 28) approach. Reconstruction was performed by primary closure (n = 5), with pedicled (n = 8) or free (n = 20) flaps.Results. According to EORTC QLQ-C30 questionnaire only positive shifts turned out to be statistically significant: general health, emotional function, pain, insomnia and diarrhea. Site-specific EORTC QLQ-H&N35 questionnaire revealed several positive (pain in the head and neck, feeling ill, use of painkillers and weight gain) and negative (public eating, problems with taste and smell, sticky saliva and dry mouth) changes. Applying algorithms for determining clinical significance changed the number and value of several scales and domains. Changes in general health, emotional function, pain, insomnia, pain in the head and neck, taste and smell disorders, mouth opening, sticky saliva, dry mouth, painkillers and weight gain were found to have some clinical relevance. Moreover, for one of them (mouth opening) statistical significance was not reached.Conclusions. Further research of clinical significance of changes and differences in scales and domains that determine and affect quality of life are needed. They will allow to understand more fully problems that every patient with oral cavity cancer tries to cope with.